2019
DOI: 10.1080/24750573.2019.1565693
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity of the perceived stress scale (PSS-10) in a sample of early childhood teacher candidates

Abstract: OBJECT: The 10-item Perceived Stress Scale (PSS-10) is one of the most widely used psychological instruments for measuring stress perception in practice and research but has sparked some controversy regarding its factor structure. Further, no study has been conducted to date using a sample of Korean university students to test the reliability and validity of the PSS and the factorial structure of this instrument. Likewise, more data on the psychometric properties of the Korean version of the scale (K-PSS-10) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…In line with the findings of previous CFA studies ( Ezzati et al., 2013 ; Lee & Jeong, 2019 ; Leung et al., 2010 ; Maroufizadeh et al., 2014 ; Ng, 2013 ; Örücü & Demir, 2009 ; Wang et al., 2011 ), the present study demonstrated that the CPSS-10 had a better fit of indices for the two-factor structure model than the one-factor structure model in people with common mental disorders.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with the findings of previous CFA studies ( Ezzati et al., 2013 ; Lee & Jeong, 2019 ; Leung et al., 2010 ; Maroufizadeh et al., 2014 ; Ng, 2013 ; Örücü & Demir, 2009 ; Wang et al., 2011 ), the present study demonstrated that the CPSS-10 had a better fit of indices for the two-factor structure model than the one-factor structure model in people with common mental disorders.…”
Section: Discussionsupporting
confidence: 92%
“…In line with the findings of previous CFA studies (Ezzati et al, 2013;Lee & Jeong, 2019;Leung et al, 2010;Maroufizadeh et al, 2014;Ng, 2013;€ Oru¨cu¨& Demir, 2009;Wang et al, 2011), the present study demonstrated that the CPSS-10 had a better fit of indices for the two-factor structure model than the one-factor structure model in people with common mental disorders. Consistent with previous findings on the correlation with symptom measures (Andreou et al, 2011;Leung et al, 2010;Maroufizadeh et al, 2014;Mills et al, 2017;Sun et al, 2019;Wang et al, 2011), the convergent and discriminant validities of the CPSS-10 were evidenced by the significant association with other outcome measures in an anticipatory direction, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…The second component, coping [31], also known as "perceived self-efficacy," is defined as the set of cognitive and behavioral strategies necessary to manage stressful situations [21]. Recently, a bidimensional model (perceived distress and perceived coping) was confirmed in a sample of early childhood teacher candidates [32].…”
Section: Discussionmentioning
confidence: 99%
“…Internal consistency in the current study was 0.87. This scale has been adapted into several languages and has been shown to have good measurement qualities (Lee & Jeong, 2019 ).…”
Section: Methodsmentioning
confidence: 99%